Keanekaragaman Jenis Herpetofauna (Ordo Squamata) di Kawasan Hutan Rawa Gambut Tropis Mangsang-Kepayang, Sumatera Selatan - Yuliany, Eka Haryati (Universitas Atma Jaya Yogyakarta, 2021)
Herpetofauna is a group of fauna consisting of amphibians and reptiles. The Squamata Order is one of the Reptiles that has the highest number of species. The Mangsang-Kepayang tropical peat swamp forest area of South Sumatra kepayang is one of the key biodiversity on the island of Sumatra. The diversity of herpetofauna can be used as a parameter of the balance and quality of the area where it lives. The problem raised in this study is how is the diversity of herpetofauna species (order Squamata) in the area of the tropical peat swamp forest of Mangsang-Kepayang, South Sumatra? Based on the problems that arise, then this study aims at the diversity of herpetofauna species (order Squamata) in the area of tropical peat swamp forest in Mangsang-Kepayang, South Sumatra. Sampling along the Boyong-Code River from upstream to downstream uses a combination of several methods, namely VES (Visual Encounter Survey), Time Search, and Road Cruising. The results obtained are 7 species of members of the Suborder Lacertilia (lizards) and 2 species of members of the Suborder Serpentes (snakes). Based on these results it can be seen that the area of Mangsang-Kepayang tropical peat swamp forest in South Sumatra is a suitable habitat for Squamata Order members.